Peningkatan Kapasitas Sumber Daya Manusia UMKM dalam Manajemen Risiko dan Adaptasi terhadap Perubahan Pasar - Muhammad Kosim; Nur Azis; Windi Windi; Nining Yuningsih (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the economy, but often find obstacles in coping with risks and adjusting to market changes. Lack of knowledge and skills in risk management can affect the sustainability of a business, especially in the midst of increasingly complicated market changes. This community service activity aims to strengthen the ability of MSME human resources (HR) to manage risks and formulate strategies to adapt to changes in the market. This activity was carried out in Central Cikarang MSMEs using interactive training and mentoring methods. The material presented consisted of an introduction to business risks, strategies to reduce risks, and adjustment actions to changes in the market, which include aspects of technology, regulations, and consumption patterns. The method applied was a combination of theory and case analysis related to the situation of MSMEs in the area. The results of the activity showed that there was an increase in the participants' understanding and awareness of the significance of risk management to maintain business continuity. Participants also gained practical skills in recognizing risks and designing adaptation plans that are suitable for the business situation they face. Through this activity, it is hoped that MSMEs can become stronger in the face of market uncertainty and be able to grow sustainably.